Adherence to the Eat-Lancet diet and its association with depression and anxiety among Iranian adults: a cross-sectional multicentric study - Tabatabaei, Ghazaal Alavi; Mohammadifard, Noushin; Haghighatdoost, Fahimeh; Rafiee, Hamed; Abbasi, Mehdi; Najafi, Farid; Farshidi, Hossein; Lotfizadeh, Masoud; Kazemi, Tooba; Roohafza, Hamidreza; Sarrafzadegan, Nizal (Frontiers in Nutrition, 2025)
BackgroundPrevious studies have shown a connection between diet and mental health. However, there is limited evidence on how emerging diets, particularly the EAT-Lancet reference diet (ELD), relate to depression and anxiety. This study aims to investigate the potential impact of ELD adherence on these mental health conditions.Methods and materialsThis cross-sectional study recruited 1,970 Iranian adults using a stratified multistage random cluster sampling method, part of a community-based investigation conducted in five cities from February 2018 to July 2019. Participants’ regular dietary intake was assessed using a validated food frequency questionnaire. The ELD was formulated based on the consumption of the 14 dietary components outlined in the ELD. Anxiety and depression were evaluated using a validated Iranian version of the Hospital Anxiety and depression Scale.ResultsIn the fully adjusted model, there was no significant association between ELD adherence and depressive symptoms (aORT3 vs. T1 = 0.89; 95% CI: 0.66, 1.19; p trend = 0.42) and anxiety (aOR T3 vs. T1 = 0.93; 95% CI: 0.70, 1.23; p trend = 0.62) in the whole population. In stratified analysis by sex, a significant inverse association was found only between ELD and depression among men (aOR T3 vs. T1 = 0.66; 95% CI: 0.40, 1.07; p trend = 0.047) but not women (aOR = 0.71, 95% CI: 0.44, 1.15; p trend = 0.103). No significant association was observed between ELD and anxiety either in men or women.ConclusionDespite a null association between ELD and depressive symptoms and anxiety in the whole population, higher adherence to ELD was associated with a lower risk of depressive symptoms in males.